Method for preparing alpha-bromoketone compound and coupling hydrogen production
The electrochemical synthesis of α-bromoketone compounds using CoS@Ti and Pt electrodes addresses the inefficiencies of traditional methods, achieving high selectivity and efficiency with cobalt sulfide catalysts on titanium mesh, suitable for scalable α-bromoketone and hydrogen production.
Patent Information
- Application Number
- CN202411301829.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-18
AI Technical Summary
Existing methods for synthesizing α-bromoketone compounds are costly, hazardous, and inefficient, often requiring expensive and corrosive reagents like platinum electrodes and strong oxidants, with low selectivity and energy efficiency.
An electrochemical method using CoS@Ti as the anode electrode and Pt as the cathode electrode, facilitating the bromoketone reaction at the anode and hydrogen evolution at the cathode, with a NaBr solution and olefin compounds in the electrolyte, achieving high selectivity and Faraday efficiency.
The method achieves selective synthesis of α-bromoketone compounds with over 90% selectivity and Faraday efficiency, scalable and compatible with hydrogen production, using a cobalt sulfide catalyst on titanium mesh.
Smart Images

Figure CN119144969A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing alpha-bromoketone compounds and coupling hydrogen production, and belongs to the field of electrochemical synthesis. Background Art
[0002] Electrosynthesis bridges the gap between traditional electrochemistry and organic chemistry and has become a promising approach for fuels, fertilizers, and drugs. α-Bromoketone is a widely used synthetic intermediate, usually derived from the bromination of carbonyl compounds, and is used in various organic reactions to synthesize agrochemicals, fine chemicals, and pharmaceuticals. Traditional industrial synthesis is to achieve α-substitution of carbonyl groups by bromine in ether in an ice-water bath, which is not only expensive in terms of substrate price and harsh in terms of reaction conditions, but also uses bromine, a highly toxic and difficult-to-use reagent. In fact, the most cost-effective synthesis method should use olefins as starting substrates to achieve one-pot synthesis (styrene ≈ 9,600 yuan / ton, acetophenone ≈ 19,200 yuan / ton). However, other reported one-step synthesis methods for α-bromoketone also require the use of excessive amounts of strong oxidants, such as H2O2, K2S2O8, TsNBr2, etc., which still have cost and hazard issues.
[0003] Electrosynthesis uses electricity to directly generate reactants or indirectly generate active intermediates (such as Br· / Br2) for transformation. According to the reaction mechanism between bromine and olefins, active bromine species usually exhibit electrophilicity and form bromonium ions, resulting in multiple reaction pathways and difficulties in selective synthesis. Recently, Qiao Shizhang et al. reported the efficient preparation of 2-chloroethanol by electrocatalytic chlorine evolution in acidic seawater, providing new clues for the halogen-mediated synthesis of α-bromohydrin and α-bromoketone. However, there has never been a direct electrochemical realization of α-bromoketone in order to achieve a one-pot electrosynthesis from olefins to α-bromoketone. Therefore, a comprehensive understanding of this system is crucial to the realization of Br - The electrophilicity and oxidative properties of its active species are key in the electrofunctionalization of olefins.
[0004] Organic workers usually use platinum, a precious metal, as an electrode to catalyze the redox reaction of bromine electrodes. However, platinum is not only expensive, but also corrodes in halogen electrolytes, which limits its widespread application. Carbon-based materials have a large specific surface area and are low in price. They are also often used as bromine electrodes in bromine batteries, but they still have problems such as high overpotential, low energy efficiency and low catalytic activity. Many works have reported the use of cobalt as an active site for bromine oxidation. For example, Zhang Bing et al. used needle-shaped NiCo2O4 as an anode catalyst to achieve a one-pot electrosynthesis of epichlorohydrin mediated by bromine free radicals. Cobalt sulfide materials with cobalt as the active center also have special redox activity. Studies have reported that CoS / CoS2@GF has a high electrochemical activity at I - / I2 redox media has better activity than Pt, and its - / Br2 redox medium shows better electrocatalytic activity and stability than other metal sulfides of the first transition series. Compared with carbon substrate, titanium mesh has better conductivity and stability in halogen environment, so loading cobalt sulfide material on titanium mesh has a better effect on Br - / Br2 redox mediators are likely to have good catalytic properties. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing α-bromoketone compounds and coupling hydrogen production in order to solve the above problems. The technical problem to be solved by the present invention is to provide an electrochemical method for synthesizing α-bromoketone compounds with high selectivity and high Faraday efficiency. CoS@Ti is used as an anode electrode and Pt is used as a cathode electrode. Under the action of current, NaBr solution and olefin compounds in the electrolyte undergo bromoketone reaction at the anode to generate α-bromoketone compounds, and platinum undergoes hydrogen evolution reaction in the cathode solution. It is an electrochemical method for synthesizing α-bromoketone compounds with high selectivity and high Faraday efficiency, and the system can be coupled with other cathode reactions such as hydrogen production.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] The present invention provides a method for preparing α-bromoketone compounds and coupling hydrogen production therewith, comprising the following steps:
[0008] An H-type electrolytic cell is used with CoS@Ti as the anode electrode and platinum as the cathode electrode. Under the action of current, the NaBr solution in the electrolyte and the olefin compounds in the electrolyte undergo α-bromoketone reaction at the anode to generate α-bromoketone compounds, and platinum undergoes hydrogen evolution reaction in the cathode solution.
[0009] Furthermore, the olefin reactant includes one or more of chain olefins, cycloolefins, aromatic olefins, and the like.
[0010] Furthermore, the α-bromoketone compounds include one or more of α-bromoketone products of chain olefins, α-bromoketone products of cycloolefins, α-bromoketone products of aromatic olefins, and the like.
[0011] Further, the NaBr solution includes a solvent and NaBr dissolved in the solvent. The solvent in the NaBr solution includes one or more of acetonitrile (CH3CN), water, n-tetrabutylammonium fluoroborate, sulfuric acid (H2SO4), etc.
[0012] Preferably, the solvent in the NaBr solution is a mixed solution of CH3CN and H2SO4 solution (aqueous solution).
[0013] Further preferably, in the mixed solution of CH3CN and H2SO4 solution (aqueous solution), the volume ratio of CH3CN to H2SO4 is 1:1-1:3, and the concentration of H2SO4 in the H2SO4 solution is 0-0.5 mol / L.
[0014] Wherein, the concentration of NaBr solution is 0.1-0.3 mol / L.
[0015] Wherein, the molar ratio of the olefin compound to NaBr is 1mmol:2.5-6mmol.
[0016] Preferably, the NaBr is added in two steps, which is conducive to the preparation of α-bromoketone with high selectivity and high Faradaic efficiency.
[0017] Preferably, the molar ratio of the olefin compound to NaBr is 1 mmol:(2.5+2) mmol.
[0018] Furthermore, the chain olefins include one or more of 1-octene, 2-octene, etc.; the cyclic olefins include one or more of cyclohexene, cycloheptene, bornene, α-pinene, β-pinene, etc.; the aromatic olefins include one or more of styrene, various substituted styrenes, allylbenzene, vinylpyridine, etc.
[0019] Furthermore, the current density is 5-20 mA / cm 2 .
[0020] Preferably, the current density is 10 mA / cm 2 .
[0021] Furthermore, the reaction time is 8-12 hours.
[0022] Preferably, the time for preparing the α-bromohydrin compound is 10-12 hours.
[0023] Furthermore, the number of reaction cycles is 1-3 times.
[0024] Furthermore, the concentration of the olefin compound in the solution is 25 mmol / L.
[0025] Furthermore, the electrolyte includes an anolyte and a cathode electrolyte, and a proton exchange membrane is provided between the anolyte and the cathode electrolyte.
[0026] Furthermore, the anode electrolyte includes a NaBr solution and an olefin compound.
[0027] Furthermore, the solvent in the cathode electrolyte includes one or more of acetonitrile, water, sulfuric acid, etc., preferably a mixture of equal volumes of 0.1 mol / L H2SO4 solution and acetonitrile.
[0028] Furthermore, the preparation method of CoS@Ti comprises the following steps:
[0029] (1) dissolving Co(NO3)2·6H2O, Al(NO3)3·9H2O, and urea in a mixture of water and n-butanol to obtain a precursor solution;
[0030] (2) The titanium mesh substrate was ultrasonically washed with acetone, H2O, 1 mol / L HCl and H2O for 10 min, 5 min, 10 min and 5 min respectively, and then transferred to the precursor solution described in step (1) for heating and cooling to obtain a cooling solution;
[0031] (3) Adding Na2S·9H2O to the cooled solution obtained in step (2), heating the solution again to generate CoS@Ti, washing the solution with H2O and anhydrous ethanol, and vacuum drying the solution to obtain the CoS@Ti electrode.
[0032] Furthermore, in the mixture of water and n-butanol, the volume ratio of water to n-butanol is 1:1.
[0033] Furthermore, the molar ratio of Co(NO3)2·6H2O and Al(NO3)3·9H2O is 3:1, and the concentrations of Co(NO3)2·6H2O and Al(NO3)3·9H2O are 0.03 mol / L and 0.01 mol / L.
[0034] Furthermore, the molar ratio of Co(NO3)2·6H2O, Al(NO3)3·9H2O, urea, and Na2S·9H2O is 3:1:10:20.
[0035] Furthermore, in step (2), the heating and cooling conditions are as follows: first heating at 120° C. for 6 hours, and then cooling to room temperature.
[0036] Furthermore, in step (3), the vacuum drying conditions are as follows: drying at 40° C. for 6 hours.
[0037] Furthermore, in step (3), the conditions for the heating reaction are as follows: stirring at a rotation speed of 1000 rpm for 0.5 h, and then heating to 120° C. and storing for 6 h.
[0038] Studies have shown that cobalt sulfide heterostructures have better Br resistance than other metal sulfides and even platinum. - / Br2-mediated catalytic performance of olefin dibromination. Therefore, further exploration of the use of cobalt sulfide heterostructures to catalyze Br - / Br2-mediated electrochemical oxidation of olefins to prepare α-bromohydrins and α-bromoketones is reasonable.
[0039] Working principle: Figure 1 As shown, the bromide ion is first oxidized to bromine at the anode. In an acidic or neutral environment, the bromo-onium intermediate generated by styrene is attacked by H2O nucleophilically to generate α-bromohydrin product. Under further oxidation, Br2 promotes the oxidation of α-bromohydrin product to α-bromoketone product. Hydrogen evolution reaction (HER) occurs at the cathode, but the use of H-type electrolytic cell avoids the pH change of the anode reaction. The Br generated at the anode - The electrochemical reaction pathway for the conversion of olefins to α-bromoketone products mediated by Br2 redox mediators is as follows:
[0040]
[0041] The reaction equation of the hydrogen evolution reaction (HER) at the cathode is: 2H + →H2↑
[0042] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages.
[0043] 1. This invention successfully constructed a highly efficient CoS@Ti self-supporting electrocatalyst for Br - / Br2-mediated electrooxidation of olefins to generate α-bromohydrin and α-bromoketone products, and paired with the cathode hydrogen evolution reaction (HER);
[0044] 2. In this reaction system, the selectivity of α-bromohydrin and α-bromoketone can reach more than 90%, and the Faradaic efficiency (FE) can reach more than 90%;
[0045] 3. CoS@Ti has good substrate scalability with the reaction system, and the H-type electrolytic cell system can be expanded to a liquid flow system in preliminary attempts, and coupled with the hydrogen evolution reaction of other cathodes, proving its technical application potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 Br - / Br2 redox mediator-mediated electrochemical reaction pathway for the conversion of olefins to α-bromoketone products;
[0047] Figure 2 SEM and XRD patterns of different materials: (a, b) SEM images of CoS@Ti (c) XRD image of CoS@Ti;
[0048] Figure 3 TEM images of CoS@Ti: (a) CoS part in CoS@Ti (b) Ti network part in CoS@Ti;
[0049] Figure 4 Comparative LSV curves of Ti mesh and CoS@Ti;
[0050] Figure 5 CV curves of CoS@Ti at different bromide ion concentrations;
[0051] Figure 6 This is a photo comparison of the actual electrocatalytic process of the electrode;
[0052] Figure 7 The results of the conversion of α-bromohydrin and α-bromoketone of different substrates;
[0053] Figure 8 SEM images of CoS@Ti after cycle reaction: (a) after the first cycle (b) after the third cycle;
[0054] Fig. 9 The XPS results of CoS@Ti after reaction under different conditions: (A) CoS@Ti is newly used to prepare α-bromoketone after α-bromohydrin (B) CoS@Ti is used to prepare α-bromoketone at the beginning of the reaction;
[0055] Fig.10 Br - Schematic diagram of the liquid flow system for the Br2-mediated electrochemical oxidation of olefins to prepare α-bromohydrin and α-bromoketone after pairing with HER or nitrobenzene reduction;
[0056] Fig.11 This is a real-life diagram of the liquid flow reaction system. DETAILED DESCRIPTION
[0057] The technical solution of the present invention is further described below in conjunction with specific embodiments and drawings, but is by no means a limitation of the present invention. Features such as preparation means, materials, structures or composition ratios not clearly described in this technical solution are regarded as common technical features disclosed in the prior art.
[0058] Materials and methods: Unless otherwise specified, reagents and materials obtained from suppliers were not further purified. The following chemicals were purchased from Sinopharm Chemical Reagent Co., Ltd. with a purity of 99%: NaBr, Co(NH2)2 (urea), n-butanol, concentrated sulfuric acid, Co(NO3)2·6H2O, Al(NO3)3·9H2O, Na2S·9H2O, and acetone. Shanghai Aladdin Biochemical Technology Co., Ltd. and Shanghai Bid Pharmaceutical Co., Ltd. provided all olefin compounds of the present invention. Gaoshi Ruilian Optoelectronic Technology Co., Ltd. provided electrodes (platinum sheet electrodes, platinum electrode clips, reference electrodes). Titanium mesh was purchased from Anping Hongyun Metal Co., Ltd.
[0059] SEM images were obtained using FEI Nova Nano SEM 450, XRD images were obtained using SHIMADAZU XRD-6100 from Shimadzu Corporation, Japan, and TEM images were obtained using FEI Talos F200X. The conversion and selectivity of substrates and products were analyzed using GC-MS-QP 2010SE. Electrochemical tests were performed using an electrochemical workstation CHI760E from Shanghai Chenhua Instrument Co., Ltd.
[0060] Example
[0061] This embodiment provides a method for electrosynthesis of α-bromoketone compounds and coupled hydrogen production therefrom.
[0062] Step 1: In-situ generation of metal sulfide catalyst on Ti mesh and electrode preparation
[0063] The CoS@Ti electrocatalyst was synthesized by in situ topological sulfurization microemulsion solvothermal method for electrocatalytic oxidation of bromide ions. 2 ) was soaked in acetone, H2O, 1mol / L HCl and H2O and ultrasonically washed for 10min, 5min, 10min and 5min respectively. 1.2mmol Co(NO3)2·6H2O, 0.4mmol Al(NO3)3·9H2O and 4mmol urea were dissolved in 15mLH2O and 15mL n-butanol to obtain a precursor solution. The precursor solution was stirred for 0.5h and then poured into a 50mL polytetrafluoroethylene liner. The cleaned titanium mesh was also placed in the polytetrafluoroethylene liner, and the liner was placed in the outer liner of the autoclave, heated to 120℃ and stored for 6h. After cooling to room temperature, a cooling solution was obtained. 8mmol Na2S·9H2O was added to the solution, stirred at 1000rpm for 0.5h, and heated to 120℃ again and stored for 6h. After cooling, the CoS-loaded titanium mesh was washed with water and ethanol several times, and then vacuum dried at 40 °C for 6 h to obtain the final CoS@Ti electrode. The loading amount of Co active sites on the Ti mesh was 11.1 mg / cm 2 First, the morphology of the synthesized CoS@Ti electrode was characterized by scanning electron microscopy (SEM). Figure 2 As shown in a and b, it is found that CoS is uniformly grown on the surface of the Ti mesh in a nanosponge-like morphology. Secondly, the CoS@Ti electrode was characterized by X-ray diffraction (XRD). Figure 2As shown in c, the CoS@Ti electrode is indeed loaded with CoS, and the peak position is marked by Δ, and the corresponding PDF card is PDF#00-019-0366. The other peaks are marked by * and #, corresponding to the Ti mesh substrate (PDF#00-044-1294) and the residual CoAl LDH (PDF#00-051-0045). Finally, the sample was sliced by focused ion beam technology (FIB) and observed under a transmission electron microscope (TEM). Figure 3 As shown in a, the CoS part presents a porous structure of flake-like stacking growth, while 3b shows a complex distribution of CoS with short-range order and long-range disorder.
[0064] Step 2: Evaluation of the electrocatalytic oxidation reaction of bromide ions using linear sweep voltammetry
[0065] CoS@Ti was directly sandwiched on a platinum electrode as a self-supporting electrocatalyst, and the platinum electrode and Hg / HgO reference electrode were used as the counting electrode and reference electrode, respectively. - The electrolyte composition of the / Br2 redox reaction was a mixed aqueous solution of 0.05mol / L NaBr and 0.1mol / L NaNO3, and the scan rate was 10mV / s. The electrocatalytic oxidation performance of CoS@Ti and Ti mesh for bromide ions was compared by linear sweep voltammetry (LSV). Figure 4 As shown in Figure 2, CoS@Ti has a significantly lower peak current potential (E p =1.450V, vs RHE) and a larger peak current density (i p =17.28mA / cm 2 ). Figure 5 It shows that when the bromide ion concentration of CoS@Ti increases, the current density increases significantly, reflecting its high Faraday efficiency. Figure 6 It can also be seen in the photo that at 1.8V RHE Under the conditions of 100 mol / L, CoS@Ti produced more Br2 than the washed Ti mesh and produced no oxygen bubbles at all, indicating that CoS@Ti has a high Faradaic efficiency. The prepared CoS@Ti was then directly used as a Br - A self-supporting working electrode (anode) for olefin functionalization reactions mediated by Br / Br2 redox reactions.
[0066] Step 3: Study the effect of different experimental parameters on the selectivity of α-bromohydrin and α-bromoketone
[0067] Since α-bromoketone derived from styrene as a template is of the greatest practical value, electrochemical experiments were conducted using styrene as a model substrate. In this reaction, dibromo products and epoxy products are the most common by-products during the electrochemical preparation process. The reaction pathway is as follows: Figure 1Therefore, by using CoS@Ti as anode and Pt as cathode, the effects of different experimental parameters on the selectivity of α-bromohydrin and α-bromoketone were investigated.
[0068] 1. Investigate the effects of solvent and pH on the formation of α-bromohydrin.
[0069] From the perspective of the reaction path, the reaction environment should be neutral to slightly acidic. Fig.10 Br - / Br2-mediated organic electrosynthesis and HER pairing diagram: Styrene (118μL, 1mmol), sodium bromide (309mg, 3mmol), n-tetrabutylammonium tetrafluoroborate (n-Bu4NBF4, 65.9mg, 0.2mmol) were added to a mixture of 20mL 0.2mol / L potassium dihydrogen phosphate and potassium hydrogen phosphate (PBS solution, pH≈6.9) and 20mL acetonitrile, and placed in the anode part of the H-type electrolytic cell, with CoS@Ti (2cm×1cm) as the anode electrode, and the actual area of the catalyst immersed in the solution was 1cm×1cm; the solution in the cathode part was 40mL PBS, and Pt (1cm×1cm) was the cathode electrode. Under the action of the current, the anode undergoes bromide ion electrocatalytic oxidation reaction and further mediates the formation of α-bromohydrin. Among them, the current density at room temperature is 10mA / cm 2 , the set time is the value of 100% Faraday efficiency (5.3h), but the actual reaction time is only 4h. This is because the phosphate ions present in the anode form Co3(PO4)2 precipitation on the CoS surface under potential polarization, destroying the Co active site and hindering the oxidation of bromide ions, so the voltage exceeds the upper limit of the workstation. Therefore, the applicant reduced the amount or concentration of PBS solution used, and found that: although the electrolysis can be completed and the substrate conversion rate is improved, the selectivity of α-bromohydrin is greatly reduced, resulting in a decrease in the actual Faraday efficiency. Therefore, it was decided to carry out the reaction in an acidic environment. When it was changed to 0.1mol / L H2SO4 solution, both the conversion rate and selectivity were greatly improved. Further increasing the concentration of sulfuric acid does not help the conversion rate, and it also helps little for the selectivity. Therefore, the systematic screening of solvents shows that a mixed solution of 0.1mol / L H2SO4 and acetonitrile (1:1) in the anode reaction chamber is an ideal solvent composition for the selective generation of α-bromohydrin.
[0070] Table 1. Solvent and pH screening.
[0071]
[0072] The initial conditions were an H-type reaction cell, the anode solution was MeCN:PBS=20mL:20mL, 1mmol styrene, 3mmol NaBr, 0.2mmol n-Bu4NBF4; the cathode solution was 40mL 0.2mol / L PBS (pH≈6.9), room temperature (rt), I=10mA, and the setting time t=20000s.
[0073] a: The reaction ends before the set time due to voltage exceeding the range (4h).
[0074] 2. Follow the above steps to investigate the effect of NaBr content on α-bromohydrin.
[0075] The electrolyte (50 μL) after the electrolysis reaction was added to dichloromethane (500 μL) for extraction. The extracted lower organic phase was taken out with a dropper and dried with anhydrous sodium sulfate. After drying, it was injected into a gas chromatography sample bottle through a syringe with a filter head, and dichloromethane was further added to make the volume 1.4 mL. The product was identified by gas chromatography-mass spectrometry (GC-MS) to quantify the conversion rate and selectivity. The results showed that when 2.5 mmol NaBr was used in 0.1 mol / L H2SO4 solution, the reaction selectivity increased significantly from 81.6% to 93.5%, which shows that the dibromo product is the main by-product in an acidic environment, so reducing the amount of bromine source can promote further increase in selectivity. However, when the bromide ion was further reduced to 2 mmol, due to its low concentration, the conversion rate was reduced to 83.3%, and the selectivity was almost not improved (93.0%). This may be due to insufficient bromine generation, resulting in a mismatch between the electrolysis rate and the bromide ion recycling rate, so the appropriate amount of NaBr is 2.5 mmol.
[0076] The conversion rate and selectivity are calculated by the following formula:
[0077] Conversion rate = sum of peak areas of all products / sum of peak areas of reactants and all products × 100%
[0078] Selectivity = GC-MS peak area of target product / sum of peak areas of all products × 100%
[0079] The Faraday efficiency (FE) calculation formula is as follows:
[0080]
[0081] The unit of the amount of reactant (n) is mol, the Faraday constant F=96485C / mol, the unit of current (I) is A, and the unit of time (t) is s.
[0082] 4. A key experimental parameter affecting the yield is the current density.
[0083] Keeping the total amount of electricity in the electrolysis process constant, the 5, 10, 15 and 20 mA / cm 2 Effect of current density on the reaction. As shown in Table 2, when 5 mA / cm 2 When the conversion rate and selectivity are 10mA / cm 2 So in terms of time efficiency (time cost), 10mA / cm 2 When the current density increases to 15mA / cm 2 When 20 mA / cm 2 The selectivity is further reduced.
[0084] Table 2 Current density screening
[0085]
[0086] The initial condition was an H-type reaction cell, the anode solution was MeCN: 0.1 mol / L H2SO4 = 20 mL: 20 mL, 1 mmol styrene, 2.5 mmol NaBr, 0.2 mmol n-Bu4NBF4; the cathode solution was 40 mL 0.1 mol / L H2SO4, room temperature (rt), t = 20000 s.
[0087] 5. Investigate the effect of time on the reaction products α-bromohydrin and α-bromoketone.
[0088] Table 3 Effect of time on the yield of α-bromohydrin and α-bromoketone
[0089]
[0090]
[0091] The initial conditions were H-type reaction cell, the anode solution was MeCN: 0.1 mol / L H2SO4 = 20 mL: 20 mL, 1 mmol styrene, 2.5 mmol NaBr, 0.2 mmol n-Bu4NBF4; the cathode solution was 40 mL 0.1 mol / L H2SO4, room temperature (rt), I = 10 mA / cm 2 , t=20000s.
[0092] As shown in Table 3, the conversion rate and selectivity increase with time within the set reaction time. At 5.56 h, the conversion rate is 100%, the selectivity is 92.6%, and the FE is 92.6%. When the reaction time is further increased, α-bromoketone product is obviously generated, and the selectivity is shown in the brackets in Table 3. When the target time for the reaction to produce α-bromoketone is reached, the yield is 56.3%.
[0093] 6. Optimization of reaction conditions of α-bromoketone.
[0094] Table 4 Optimization of reaction conditions for α-bromoketone
[0095]
[0096] The initial conditions were an H-type reaction cell, in an air atmosphere, the anode solution was MeCN: 0.1 mol / L H2SO4 = 20 mL: 20 mL, 1 mmol styrene, 3 mmol NaBr, 0.01 mol / L n-Bu4NBF4; the cathode solution was 40 mL 0.1 mol / L H2SO4, room temperature (rt), I = 10 mA, and the set time t = 40000 s.
[0097] As shown in Table 4, the selectivity of α-bromoketone is also improved after the increase of bromine content. This may be because 1mmol of 2.5mmol bromine enters the product, and only 1.5mmol bromine content is still present in the electrocatalytic oxidation. The oxidation rate of bromine active species during subsequent oxidation is inconsistent with the electrochemical reaction rate, so it is difficult to ensure the high selectivity of the reaction. So an attempt was made to further increase the amount of sodium bromide added, and the selectivity of 3mmol NaBr was improved, but the selectivity of 5mmol NaBr was reduced. It can be seen from the results of GC-MS that the increase in the amount of bromide ions leads to the generation of a larger amount of dibromo products. In combination with the above experiments, the applicant chose to add sodium bromide in two steps to achieve the preparation of α-bromoketone with high selectivity and high Faraday efficiency, with a yield of 90.7%.
[0098] Step 4: Explore the conversion and selectivity of different olefin compounds
[0099] Except for replacing different olefin compounds as the starting reactants, the α-bromoketone reaction was carried out in the same manner as in this example. The results are shown in FIG. Figure 7 As shown ( Figure 7Pro-1 refers to the generation of α-bromo ketone, Pro-2 refers to the generation of α-bromo alcohol, and the former is the conversion rate and the latter is the selectivity in 90.7% / 90.7% as shown in reactant 1). The substrate expansion results show that the method of the present invention can successfully prepare a variety of compounds of α-bromo alcohol and α-bromo ketone, and the conversion rate and selectivity of the olefin compound will be affected by the solubility of the reactant in the solvent given in the example. Generally, the introduction of a strong electron-withdrawing group on the benzene ring and the increase in the number of carbon atoms in the alkyl olefin will lead to a decrease in its solubility, while the introduction of an electron-donating group on the benzene ring has little effect on the solubility.
[0100] Step 5: Explore the cyclic performance or scale-up experiment of the catalyst and catalytic system
[0101] 1. Investigate the cyclic performance of the catalyst in the preparation of α-bromoketone.
[0102] After the reaction of α-bromohydrin, the CoS on the surface tends to be converted into the needle-like CoO reported in the literature. x , and then further generate book-shaped Co3O4, such as Figure 8 The results of X-ray photoelectron spectroscopy (XPS) show that the surface Co-S is increasingly converted into Co-O, such as Fig. 9 B. It is noteworthy that the recovered catalyst showed good stability during the three uses, with the applied voltage remaining almost unchanged (about 1.8 V RHE ), and the yields were maintained above 80%. If the preparation of α-bromoketone is continued, more cobalt oxide will cover the CoS surface. However, if new CoS@Ti is used to prepare α-bromoketone directly after the formation of α-bromohydrin, due to the strong oxidizing nature of the system, the CoS on the surface will completely disappear after the reaction, making the catalyst ineffective. Fig. 9 A. These results indicate that Br2 plays an oxidizing role in the formation of α-bromoketone, while the Co3O4 formed during the reaction is beneficial to protect the internal CoS. In order to extend the service life of the catalyst, it is necessary to use the catalyst continuously in the preparation of α-bromoketone.
[0103] 2. Investigate the cyclic performance of the catalytic system in the preparation of α-bromoketone.
[0104] In addition to focusing on the recycling properties of the material, the sustainability of the reaction solution in different systems was also studied in depth, which is often overlooked in traditional organic reactions. However, in the preparation system of α-bromoketone, by reintroducing the same amount of NaBr (2.5mmol+2mmol) and styrene (1mmol) as the initial reaction conditions and applying current, the reaction can still proceed smoothly, and the selectivity (88.1%) and yield (88.1%) are maintained well. After three cycles, the gram-scale synthesis of α-bromoketone (1.03g) was successfully achieved.
[0105] 3. Experimental investigation of the liquid flow system and cathode coupled hydrogen evolution reaction and its derivatives.
[0106] Since the preparation system of α-bromoketone is an H-type electrolytic cell, it is considered to couple the reaction system through a liquid flow electrolytic cell device. The liquid flow circulation system can achieve the coupling of α-bromohydrin or α-bromoketone with the cathode hydrogen evolution reaction, and even the coupling of the selective electroreduction reaction of nitrobenzene derived from the hydrogen evolution reaction. At 10mA / cm 2 At a current density of , the yields of α-bromohydrin and α-bromoketone are both above 90% for both hydrogen evolution reaction and nitrobenzene reduction reaction. The amount of hydrogen evolved is collected by drainage method. The device is shown in the figure below. Fig.11 As shown; the reaction progress of nitrobenzene and the reaction products were detected by GC-MS.
[0107] The experiment was conducted based on the preparation of 1mmol α-bromoketone product: when coupled with hydrogen evolution reaction, the maximum input voltage at both ends of the cathode and cathode did not exceed 3.0V, the maximum energy consumption was 600J (corresponding to α-bromohydrin) and 1200J (corresponding to α-bromohydrin), and the amount of H2 collected in the experiment was about 21.5mL and 45.0mL, which was basically consistent with the input power; when coupled with nitrobenzene reduction, the cathode solution was in the preferred cathode hydrogen evolution solution (acetonitrile and 0.1mol / L dilute sulfuric acid solution were mixed in a volume ratio of 1:1), and nitrobenzene was added. The selectivity and conversion rate of the selectively generated azobenzene oxide were 86.4% and 58.2% (corresponding to α-bromohydrin, adding 1mmol nitrobenzene), 66.9% and 65.6% (corresponding to α-bromoketone, adding 1mmol nitrobenzene). This result illustrates the efficient electrosynthesis ability of the H-type electrolytic cell coupled with the cathode reaction in this method, which provides more possibilities for improving the comprehensive utilization efficiency of electrons.
[0108] The above is a description of the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above-mentioned description of the embodiments for the convenience of ordinary technicians in the technical field to understand and use the invention. It is obvious that those familiar with the technology in the field can easily make various modifications to these embodiments and apply the general principles described here to other embodiments without creative work. Therefore, the present invention is not limited to the above-mentioned embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.
Claims
1. A method for preparing α-bromoketone compounds and coupling hydrogen production, It is characterized in that The following steps are involved: With CoS@Ti as the anode electrode and platinum as the cathode electrode, under the action of current, the NaBr solution in the electrolyte and the olefin compounds in the electrolyte undergo α-bromoketone reaction at the anode to generate α-bromoketone compounds, and platinum undergoes hydrogen evolution reaction in the cathode solution; The α-bromoketone compounds include one or more of α-bromoketone products of chain olefins, α-bromoketone products of cycloolefins, and α-bromoketone products of aromatic olefins.
2. The method for preparing α-bromoketone compounds and coupling hydrogen production according to claim 1, It is characterized in that The solvent in the NaBr solution includes one or more of acetonitrile, water, n-tetrabutylammonium tetrafluoroborate, and sulfuric acid.
3. The method for preparing α-bromoketone compounds and coupling hydrogen production according to claim 2, It is characterized in that The NaBr concentration in the anode solution is 0.1-0.3 mol / L, and the sulfuric acid concentration is 0-0.5 mol / L.
4. The method for preparing α-bromoketone compounds and coupling hydrogen production according to claim 1, It is characterized in that The solvent in the cathode electrolyte includes one or more of acetonitrile and aqueous sulfuric acid solution.
5. The method for preparing α-bromoketone compounds and coupling hydrogen production according to claim 1, It is characterized in that The olefin compound includes one or more of chain olefins, cycloolefins and aromatic olefins.
6. The method for preparing α-bromoketone compounds and coupling hydrogen production according to claim 4, It is characterized in that The olefins include one or more of 1-octene and 2-octene; The cyclic olefins include one or more of cyclohexene, cycloheptene, norbornene, α-pinene, and β-pinene; The aromatic olefin includes one or more of styrene, substituted styrene, allylbenzene and vinylpyridine.
7. The method according to claim 1, It is characterized in that The current density is 5-20 mA / cm 2 .
8. The method according to claim 1, It is characterized in that The time of the α-bromo ketonization reaction is 4-12 hours, and the number of electrolyte cycles of the α-bromo ketonization reaction is 1-3 times.
9. The method for preparing α-bromoketone compounds and coupling hydrogen production according to claim 1, It is characterized in that The molar ratio of the olefin compound to the NaBr in the NaBr solution is 1 mmol:2-6 mmol.
10. The method for preparing α-bromoketone compounds and coupling hydrogen production according to claim 1, It is characterized in that The preparation method of CoS@Ti comprises the following steps: (1) Put Co(NO 3 ) 2 6H 2 O、Al(NO 3 ) 3 9H 2 O, urea is dissolved in a mixture of water and n-butanol to obtain a precursor solution; (2) ultrasonically washing the titanium mesh substrate, transferring it to the precursor solution obtained in step (1), heating it, and cooling it to obtain a cooling solution; (3) Add Na to the cooled solution obtained in step (2) 2 S·9H 2 O, and then heated and reacted again to generate CoS@Ti, which was then cleaned and dried in vacuum to obtain the CoS@Ti electrode.
Citation Information
Patent Citations
Process for the manufacture of new n-oxacyclic- alkyl-piperidyl-diazacompounds
CA1117941A
Method for synthesizing alpha-brominated aromatic ketones compound
CN102503751A
Electrochemical catalytic synthesis method of alpha-carbonyl ketone compounds
CN104313635A
Method and device for preparing epoxy compound through electrochemical bromine alcohol method and application
CN117845238A
Preparation of selected epoxides
GB8310260D0
